Postage stamp commemorating the 10th anniversary of the Korea Institute of Science and Technology (1976)
Stamp depicts aspects of chemistry and related sciences.
Keywords: Korea (South); Postage stamps; Chemistry; Science on postage stamps; Han'guk Kwahak Kisul Yŏn'guso